2022
DOI: 10.1016/j.bioactmat.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patches for rotator cuff repair: A systematic review and meta-analysis based on animal studies

Abstract: Based on the published animal studies, we systematically evaluated the outcomes of various materials for rotator cuff repair in animal models and the potentials of their clinical translation. 74 animal studies were finally included, of which naturally derived biomaterials were applied the most widely (50.0%), rats were the most commonly used animal model (47.0%), and autologous tissue demonstrated the best outcomes in all animal models. The biomechanical properties of naturally derived biomaterials (maximum fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 159 publications
0
10
1
Order By: Relevance
“…Although our results of the autograft group were consistent with those of Liu et al 38 and Adams et al, 2 these findings should be interpreted with caution, as previous studies only compared autografts with simple sutures, allografts, or different types of autografts. 53 Consequently, our study indicated that at least the knitted PET patch was not inferior to the autologous tendon in early tendon healing after bridging reconstruction.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Although our results of the autograft group were consistent with those of Liu et al 38 and Adams et al, 2 these findings should be interpreted with caution, as previous studies only compared autografts with simple sutures, allografts, or different types of autografts. 53 Consequently, our study indicated that at least the knitted PET patch was not inferior to the autologous tendon in early tendon healing after bridging reconstruction.…”
Section: Discussionmentioning
confidence: 60%
“…5,34 Most animal studies have focused on degradable synthetic materials for patch augmentation, such as polycaprolactone (PCL), polylactic acid (PLA), poly(L-lactide) (PLLA), 15,24,57 and poly(lactic-co-glycolic acid) (PLGA), which show better outcomes than simple sutures. 53 Despite the satisfactory biocompatibility and high porosity of degradable synthetic patches, the decrease in mechanical properties may lead to uneven loading or repair failure, 34 thus limiting their application in clinical bridging reconstruction of MRCTs. Nondegradable synthetic materials, such as polyester, polyurethane urea, polytetrafluoroethylene, and polypropylene, have outstanding mechanical strength as well as long-term mechanical support, 11,13,40,41,44,45,48 whereas their hydrophobic property and inferior biocompatibility may lead to poor healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 articles [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ] are included in this special issue. These articles can be categorized in terms of authors, biomaterials and targeted clinical areas, and article types.…”
mentioning
confidence: 99%
“…As an emerging field, regulatory science has been gradually developed to play an important role during the translation of innovative biomaterial-based medical products. Several articles in this special issue are on regulatory science and discuss the new standards, tools, and approaches to evaluate the safety, efficacy, quality, and performance of medical products [ 10 , 13 , 17 , 19 ]. This special issue also covers a wide range of article types including research article [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , 11 , 12 , 15 , 16 , [18] , [19] , [20] , [23] , [24] , [25] , [26] ], reviews [ 14 , 17 , 21 , 22 , 27 ], perspectives [ 10 , 13 ] and opinion paper [ 18 ].…”
mentioning
confidence: 99%